Sandifer Syndrome Case Report: An Unusual Presentation with Paroxysmal Torticollis - Giorgia Segre; Martina Penzo; Giovanna Zorzi; Federica Graziola (Reports)
Background and Clinical Significance: Sandifer syndrome is an uncommon manifestation of gastroesophageal reflux disease, characterized by paroxysmal episodes of abnormal posturing, particularly involving the neck and upper body, often associated with underlying esophageal discomfort. Case Presentation: In this report, we present a 16-month-old infant who exhibited multiple daily paroxysmal episodes of atypical head posturing, primarily tilted to the right, each lasting less than 10 s, with spontaneous resolution. Notably, these episodes lacked other neurological or systemic symptoms, and the clinical presentation differed from classical descriptions of Sandifer syndrome, which often include more prolonged dystonic posturing or correlation with feeding. The diagnosis was supported by the resolution of symptoms following the administration of a proton pump inhibitor, highlighting the importance of recognizing this condition in infants with unexplained posturing behaviors. Conclusions: This case emphasizes the variability in clinical manifestations of Sandifer syndrome and underscores the need for a high index of suspicion, as timely management of gastroesophageal reflux disease can lead to complete symptom resolution and prevent unnecessary neurological investigations.